Proactive therapeutic drug monitoring of infliximab: a comparative study of a new point‐of‐care quantitative test with two established ELISA assays. Issue 7 (10th August 2016) - Afonso, J.; Lopes, S.; Gonçalves, R.; Caldeira, P.; Lago, P.; Tavares de Sousa, H.; Ramos, J.; Gonçalves, A. R.; Ministro, P.; Rosa, I.; Vieira, A. I.; Dias, C. C.; et al.
Summary: Background: Therapeutic drug monitoring is a powerful strategy known to improve the clinical outcomes and to optimise the healthcare resources in the treatment of autoimmune diseases. Currently, most of the methods commercially available for the quantification of infliximab (IFX) are ELISA‐based, with a turnaround time of approximately 8 h, and delaying the target dosage adjustment to the following infusion. Aim: To validate the first point‐of‐care IFX quantification device available in the market – the Quantum Blue Infliximab assay (Buhlmann, Schonenbuch, Switzerland) – by comparing it with two well‐established methods. Methods: The three methods were used to assay the IFX concentration of spiked samples and of the serum of 299 inflammatory bowel diseases (IBD) patients undergoing IFX therapy. Results: The point‐of‐care assay had an average IFX recovery of 92%, being the most precise among the tested methods. The Intraclass Correlation Coefficients of the point‐of‐care IFX assay vs. the two ELISA‐based established methods were 0.889 and 0.939. Moreover, the accuracy of the point‐of‐care IFX compared with each of the two reference methods was 77% and 83%, and the kappa statistics revealed a substantial agreement (0.648 and 0.738). Conclusions: The Quantum Blue IFX assay can successfully replace the commonly used ELISA‐based IFX quantification kits. This point‐of‐care IFX assay is able to deliver the results within 15 min makes it ideal for an immediate target concentration adjusted dosing. Moreover, it is a user‐friendly desktop device that does not require specific laboratory facilities or highly specialised personnel.